Pembuatan Simulasi Perang Zaman Pertengahan dengan Metode Pose to Pose Menggunakan Software Blender - Annisa Rizkiana Putri; Seta Murdha Pamungkas; Ikhwata Andy Pratama; Naila Nahdiyah; Cahya Wulandari; Juniardi Nur Fadilah; Fresy Nugroho (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
The animating process is a process in making animation. Many animations seem less clear in delivering messages to the audience. This is because the images and motion of the animation are less real. In making animations, methods are needed to produce quality movements. The method of making animated motions varies depending on the animation pattern you want to create. This research will discuss the Pose to Pose method and will be implemented in the process of making 3D animation that tells the second crusade. The process of warfare involving many people will be in this animation. This method is used in basic human movements in the story. So that the animation looks more real. In making this animation utilizing Blender software starting from the initial stage of manufacture to completion.